A chromosome 9 deletion in Plasmodium falciparum results in loss of cytoadherence - D. J. Kemp; J. Thompson; D. A. Barnes; T. Triglia; F. Karamalis; C. Petersen; G. V. Brown; K. P. Day (Memorias do Instituto Oswaldo Cruz, 1992)
Many lines of Plasmodium falciparum undrgo a deletion of the right end of chromosome 9 during in vitro culture accompanied by loss of cytoadherence and gametocytogenesis. Selection of cytoadherent cells from a mixed population co-selects for those with an undeleted chromosome 9 and selected cells produce gametocytes. The deletion also results in loss of expression of PfEMP1, the putative cytoadherence ligand, suggesting PfEMP1 or a regulatory gene controlling PfEMP1 expression and gametocytogenesis may be encoded in this region. We have isolated several markers for the deleted region and are currently using a YAC-P. falciparum library to investigate this region of the genome in detail.